BUDAYA ORGANISASI DAN KOMITMEN MANAJEMEN TERHADAP PIPK: STUDI KASUS PADA OMBUDSMAN REPUBLIK INDONESIA - Khomaeni, Ahmad; Ristanti, Almah; Pratiwi, Permata Dian (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
Internal Control over Financial Reporting (PIPK) is essential for ensuring financial accountability in government institutions. The Ombudsman of the Republic of Indonesia faces challenges in implementing PIPK due to limited resources and budget constraints. This study examines how organizational culture and management commitment influence PIPK implementation. Using a qualitative case study approach, data were gathered through interviews with senior management, internal auditors, and finance staff. Thematic analysis revealed that strong management commitment significantly enhances the effectiveness of PIPK. However, inconsistent organizational culture, low employee engagement, and rigid hierarchical structures present notable obstacles. Furthermore, poor interdepartmental coordination hinders the standardization of internal control practices. The study recommends fostering a culture of compliance through strong leadership, ongoing training, and improved communication. These efforts are crucial to enhancing accountability and transparency, particularly in resource-constrained institutions.